A taste of health the connection between eating and health - Willumsen, Gail.; WQED (Television station : Pittsburgh, Pa.). (Pittsburgh, Pa. WQED [production company], 1991)
Shows how diet has direct effect on health. A look at scientific gathering preliminary evidences of a genetic link between health and diet. Cross cultural studies and cholesterol research are addressed.
VHS.
Credits: Host, Joel Grey.
Keywords: Health; Diet; Indians -- Food; Nutrition